ANALYSIS OF THE RELATIONSHIP BETWEEN PRICES, PROMOTIONS, VARIANTS OF PRODUCTS AND SALES VOLUME IN LEGO BRAND TOY PRODUCTS IN GRAND CITY SURABAYA - Asrul Ramadhanni; Arasy Alimudin (NAROTAMA UNIVERSITY, Indonesia, 2018)
This study aims to analyze the relationship between price, promotion, product variants, and sales volume of Lego branded toy products at Grand City Surabaya. This research is quantitative. Population and sample based on distributing questionnaires to consumers or customers of Lego brand products in Grand City Surabaya and a sample of 100 respondents was taken. Data collection techniques using observation, interviews, and documentation. The data analysis used was a validity test, reliability test, and chi-square test. The results showed that price, promotion, and product variants had a significant relationship with sales volume which had a significant value <0.05. The indicator of interest in the implementation of a promotional event from the promotional variable is the most very significant and has a significant value of 0.000. So the variable price, promotion, and product variants have a good relationship with sales volume so that sales levels are stable and increasin